Breakthrough discoveries in information technology research [ advancing trends - Khosrowpour, Mehdi , 1951- (Gale virtual reference library, 2010)
"This book informs researchers and practitioners of novel and emerging research in information science and technology, allowing for the discussion and dissemination of critical concepts that will promote further study and innovation"-- Provided by publisher